Percepções de uma estudante surda sobre suas vivências no ensino médio - Dias, Vitor de Souza (2023)
The aim of this study is to analyze, together with a deaf student who has completed high school, their perceptions regarding accessibility in this educational stage. In light of the bilingual educational proposals outlined in Decree 5,626/2005 and Law 14,191/2021, and with the presence of sign language interpreters and translators, it is expected that schools are prepared to adequately accommodate these students, particularly in high school, which aims to prepare students for their professional life and university entrance. However, educators do not always possess the necessary preparation for this, which can hinder accessibility and knowledge acquisition, as well as impact the future choices of deaf students. Thus, this is qualitative research utilizing semi-structured online interviews as the data collection instrument. The participant is a young deaf individual, who graduated from high school three years ago at a Federal Institute in São Paulo, Brazil, and currently studies pedagogy at a university in the same state. Two interviews were conducted to understand this student's perception of accessibility and the factors influencing their subject-related preferences and areas of interest. Three analytical categories were developed, covering: accessibility in high school, subject-related affinities, and school relationships. The analyses revealed that educators can implement strategies, such as using conceptual maps and images related to concepts, to enhance visual and accessible teaching. Additionally, the affective factor was noted to be crucial in relation to subject preferences and interpersonal relationships in school. This study is expected to contribute to further research in the field of special education and deaf education, particularly concerning accessibility for deaf students in high school, an area that still lacks in-depth discussions.